Saung Angklung Udjo: Invensi Tradisi Lokal yang Mendunia - Budiman Mahmud Musthofa; Jajang Gunawijaya (Antropologi Indonesia, 2017)
The globalization of culture presents new challenges for society to be more creative in managing local culture and tradition. The various impact of this globalization might be anticipated if the creative process continues in the community. Through qualitative method, this study examines Saung Angklung Udjo (SAU) as an example of the achievement on the creative process through invention of tradition in developing art traditions. SAU as an invention of tradition strongly associated with the individual agency’s role in responding the reality of the arts tradition through the establishment of angklung workshop. Individual agencies design the social and environmental conditions by creating angklung workshop. This workshop represents the art tradition of angklung as part of Sundanese culture. The ability of individual agents in creating invention of tradition through formalization and ritualization of educational activities, production and angklung performances could be a model for art traditions practitioners to stay creative in facing the challenges of cultural globalization.Keywords: Cultural Globalization, Invention of Tradition, Arts Traditional, Saung Angklung Udjo